The effects of question, respondent and interviewer characteristics on two types of item nonresponse - Henning Silber; Joss Roßmann; Tobias Gummer; Stefan Zins; Kai Willem Weyandt (Journal of the Royal Statistical Society: Series A (Statistics in Society), 2021)
In this article, we examine two types of item nonresponse in a face-to-face population survey: `don't know' (DK) and `item refusal' (REF). Based on the cognitive model of survey response, the theory of survey satisficing and previous research, we derive explanatory variables on three levels: question, respondent and interviewer characteristics. The results of our cross-classified model show that while the two levels question and respondents' characteristics affected both types of item nonresponse, interviewer characteristics affected only DK answers. Our results also confirm that DK and REF are substantially different item nonresponse types resulting from distinguishable disruptions of the cognitive response process. Since most results are in line with prior theoretical predictions, they suggest that survey practitioners are well-advised by continuing to follow the large body of practical guidance derived from the theories tested here.
Keywords: 519; cognitive response process; do not know answers; item refusals; measurement error; question design; response behaviour